2022
DOI: 10.3389/fpsyg.2022.888714
|View full text |Cite
|
Sign up to set email alerts
|

Status and Influencing Factors of Social Media Addiction in Chinese Medical Care Professionals: A Cross-Sectional Survey

Abstract: BackgroundIn modern society, social media addiction (SMA) has become a serious problem in many countries, including China. Almost every medical care professional has their own social media account. They are also at risk for SMA, but no SMA studies in Chinese medical care professionals have been published. This study aims to investigate the status and influencing factors of SMA among Chinese medical care professionals.MethodsA cross-sectional study was conducted among 519 physicians and nurses from two randomly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 108 publications
(151 reference statements)
1
2
0
Order By: Relevance
“…The study results showed that our study sample was highly addicted to social media. Similar to the previous study, that found nurses, students and medical doctors were affected by social media addiction (Luo et al, 2022). In this study, the association between psychological distress and social media addiction was significant.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The study results showed that our study sample was highly addicted to social media. Similar to the previous study, that found nurses, students and medical doctors were affected by social media addiction (Luo et al, 2022). In this study, the association between psychological distress and social media addiction was significant.…”
Section: Discussionsupporting
confidence: 89%
“…In addition, it has been known that social media can help people, with anxiety and shyness, to feel supported and understood by their peers (Marino et al, 2018). Indeed, it could also be argued that the increasein social media addiction can have detrimental effects on the general well-being of people (Luo et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the score of the three components of EE, CY, and PA were 10.73 ± 6.41, 6.74 ± 5.27, and 17.95 ± 7.83, respectively. According to previous studies, during the COVID-19 epidemic in China, vaccination staff had lower scores of EE and CY but higher scores of PA than other health professionals ( 19 , 48 , 65 , 66 ). The results were consistent with the distribution of high levels of EE, CY, and low levels of PA in vaccination staff and medical staff discussed above.…”
Section: Discussionmentioning
confidence: 91%